Damage for loss of future earning for foreign workers in Malaysia: A lesson to be learned from Singapore - Mahdzir, Nazli (2013)
True to the concept of justice and equality, the law on the assessment of damages for loss of future earnings in Malaysia do not differentiate between the classes of people claiming for compensation.Section 28A (2) of the Civil Law Act 1956 (Act 67)provide similar method of assessment for both Malaysian and foreign workers working in Malaysia.This paper discusses the possibility of over-compensating the foreign workers especially those coming from countries with lower income level than Malaysia.The study finds that the law in Malaysia leave no avenue for judges to adjust the assessment of damages for loss of future earnings to take into account the possibility that these workers will be returning to their home countries before the end of their working life and in all probability earning less than what they were receiving in Malaysia. Because of this rigidity in our law, the foreign workers will receive damages for loss of future earning in the amount which represent their income as if they would be earning the same income throughout their working life. Therefore it is hoped the proposal to amend the provisions regarding the assessment of damages for personal injury and fatal accident claims in the Civil Law Act 1956 currently being considered by the Law Revision and Law Reform Division of the Attorney General Chambers will take into account this phenomenon and formulate suitable method to prevent over-compensation.